THE EFFECT OF PRODUCT QUALITY, INNOVATION AND PRICE TO PURCHASING DECISIONS OF NOOLDE PRODUCTS - LISA ADETIYA; GINANJAR RAHMAWAN (CV KULTURA DIGITAL MEDIA, 2021)
The purpose of this study was to determine the effect of product quality, the effect of product innovation, and the effect of price perceptions on purchasing decisions. This study uses non probability sampling techniques and purposive sampling approach with the variabels of product quality, product innovation, and price perceptions. The population is consumers of Indomie brand instant noodle products who are in Klaten Regency and have consumed Indomie brand instant noodle productsat least 3 times. This study uses a sample of 100 respondents with data collection using a questionnaire. Based on the research results, it is hoped that Indomie will be able to maintain its quality, add new and more unique innovations, and maintain prices that can be reached by all the general public.